Trivialising humour and naturalising stereotyping: The impact ofmemes on narratives of xenophobia, machismo, and narcoculture - Wilches Tinjacá, Jaime Andrés (2025)
Nowadays, the digital revolution has positioned the meme as a manifestation of humour that constructs and reflects worldviews that inhabit the collective imaginaries of the communities that share and viralise them. In this sense, the present study aims to analyse 300 memes obtained from the algorithmic operations of Google Images around three specific themes: xenophobia, sexism (machismo), and narcoculture. Amethod based on the coding of memetic narratives was employed, which enabled us to break down the form and message of each piece of communication in terms of its structure, intertextuality, intention, the rhetoric of humour, narrative, and main character. The results indicate that memes, within their textual and visual nature, are used both to ridicule or reinforce stereotypes but can also serve to denounce complex social issues within the selected contexts. The discussion questions the role of institutions and digital platforms in regulating discourses that circulate through memes, especially when they reinforce problematic narratives or promote discrimination. The research underlines the need to move towards processes of memetic literacies, which avoid underestimating the role of these communicativepieces that, mimetised in humour, can reproduce identities prone to discourses of hate, exclusion, and apology for illegality.